Compliance to treatment and its role in solving the problem of uncontrolled hypertension - V. I. Podzolkov; A. E. Bragina; I. D. Medvedev; M. V. Vetluzhskaya; A. A. Abramova; I. Zh. Loria; N. K. Megeneishvili; A. V. Sutulova (Кардиоваскулярная терапия и профилактика, 2023)
Failure to achieve blood pressure targets and insufficient control are important cardiology problems that remain relevant despite well-defined and generally available modern algorithms for the treatment of hypertension (HTN) and the availability of effective antihypertensive drugs. The level of hypertension control in Russia remains quite low and is 14,1% for men and 30,9% for women. The generally recognized most important factor determining the low blood pressure control is non-compliance with antihypertensive therapy, which, in turn, determines the high percentage of uncontrolled HTN among patients. The review discusses the most common causes of low adherence to treatment. Particular attention is paid to the doctor’s ability to remove barriers to adherence and errors in the choice of therapy, including insufficient prescribing of fixed-dose combinations. The review presents a modern view on the significance of combined antihypertensive therapy. Attention is focused on fixed-dose combinations of antihypertensives, the use of which significantly increases adherence to therapy, and the unique properties and effectiveness of lisinopril, amlodipine and indapamide are described.